Tailoring: The Healthiest Profession –An observational Retrospective study (Academia Journal of Medicine, 2025)
Background: - It is a proven fact that the job involving sitting for long hours leads to increase in mortality1 and morbidity2 and is one of the major causes of life style diseases. However recently, it is proven that calf muscle pushup3 while sitting causes improved blood sugar level and even fidgeting4,5of legs while sitting has many health benefits and potential to prevent life style diseases. While the tailoring job involves sitting for long hours, but at the same time, action of their feet to make sewing machine work, is synonymous to calf muscle pushups. To work on the sewing machine, they have to continuously move their feet on foot pedal of the machine while sitting. The purpose of this retrospective observational study is to find out if the adverse effect due to long hours of sitting can be mitigated by calf muscle pushups and leg fidgeting. Aim.: To find the status of health condition of tailors (working on sewing machine with foot pedal) Material and Methods Sample Size: A total sample size of 250 tailors from and nearby Kurti Nagar, Meerut UP India, which is the major hub of tailoring business was considered for this study. Tailors of every age group were included (with no age criteria). There were no exclusion criteria. Questionnaire-The following questions were asked from the tailors and the response was recorded through videography. Results: The study revealed that none of the 250 tailors reported any health issues or use of medication. The consistent movement of the feet during tailoring work appeared to have a protective effect against the adverse outcomes of prolonged sitting. Discussion & Conclusion: This study highlights tailoring as a potentially healthier profession among sedentary jobs, owing to the inherent physical activity of operating a sewing machine’s foot pedal. The findings suggest that integrating similar movements into other sedentary occupations could mitigate health risks associated with prolonged sitting.
Keywords: Tailoring; sedentary behavior; calf muscle push-ups; leg fidgeting; lifestyle diseases; health benefits; foot pedal; prolonged sitting